Osteoclastogenesis in Periodontitis: Signaling Pathway, Synthetic and Natural Inhibitors - Ketherin, Ketherin; Sandra, Ferry (Molecular and Cellular Biomedical Sciences, 2018)
Osteoclast activities are responsible for the resorption of bone cells found in several bone diseases, one of which is periodontitis and arthritis. The downregulating signals of Receptor Activator of Nuclear Factor kB (RANK)-RANK Ligand and Tumor Necrosis FactorÂ  (TNF)-a are the major cause of the bone destruction. Studies and experiments have been performed to overcome this matter. Various medications are now available to treat bone-related diseases, targeting the specific aspect of the signaling. Synthetic drugs such as denosumab and bisphosphonates have complex pharmacological action and have been the leading choice in treatment. Evidence in studies proved that natural resources including herbal products have potential application to therapy for bone loss, with caffeic acid and Caffeic Acid Phenethyl Ester (CAPE) showing significant inhibitory results and Chinese herbs such as Herba epimedii (YÃn YÃ¡ng HuÃ²) and Fructus psoraleae(BÇ GÇ ZhÄ«) proved to contain components that give similar effects to estrogen. The purpose of this review is to discuss the therapy value of available synthetic and natural therapeutic agents. Understanding the mechanisms of both agents will not only clarify their function as therapeutic agents, but can also be the key to the treatment of diseases caused by bone resorption by targeting specific aspects of osteoclastogenesis.Keywords: osteoclastogenesis, TNF, RANKL, bone resorption, natural resource, signaling, treatment